Dynamic Adjustment of Transmission Power of Mobile Ad-Hoc Wireless Sensor Networks - Hoeller, Arliones; Oliveira, Peterson; Fröhlich, Antônio Augusto (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2013)
A Wireless Sensor Network (WSN) is composed by many tiny embedded systems with sensing, processing and communication capabilities. These sensors use limited power sources, such as batteries, making energy a key resource that needs management. One of the main contributors to energy consumption in WSN nodes is data transmission through a radio device, and the parameter that most influences energy consumption in radio devices is the transmission power. In this work, we explore the Ant-Colony Optimization (ACO) mechanism of the Ant-based Dynamic Hop Optimization Protocol (ADHOP) routing algorithm to minimize transmission power of the links in a route without compromising connectivity. The proposed mechanism is evaluated through simulation using the OMNeT++ simulator with the INETMANET framework for mobile IEEE 802.15.4 networks. The results confirm the initial assumption that it is possible to lower energy consumption with little impact on data delivery rate.